Association of Neighborhood‐Level Area Deprivation with Demographics and Outcomes in Oropharyngeal Squamous Cell Carcinoma - Shravan Asthana; Asher C. Park; Abhinav Talwar; Kirsten B. Burdett; Christopher Puchi; Ahmed Ibrahim; Olivia Dunne; Urjeet Patel; Sandeep Samant; Katelyn O. Stepan (OTO Open)
Abstract Objective To characterize neighborhood‐level area deprivation's association with oropharyngeal carcinoma clinicodemographics, tumor staging, recurrence, and overall survival. Study Design Retrospective study. Setting Single institution academic medical center. Methods Patients diagnosed with oropharyngeal squamous cell carcinoma (OPSCC) between 2007 and 2022 at our institution were included in this study. The Area Deprivation Index (ADI) was used to quantify neighborhood‐level disadvantage based on patients’ primary residence at the time of their diagnosis. Continuous variables were compared between groups using the Wilcoxon rank sum test. For categorical variables, proportions were compared using Fisher's exact test. Overall survival (OS) and recurrence‐free survival (RFS) distributions were estimated using the Kaplan‐Meier method and log‐rank test. OS and RFS were further assessed by univariable and multivariable analyses performed using the Cox proportional hazards model. Results The higher ADI (more disadvantaged) group consisted of a significantly greater proportion of Black race (P < .001), 10+ pack‐year smoking history (P = .003), and Medicare patients (P = .018). On logistic regression analysis, neither ADI nor other social factors were significantly associated with increased likelihood of advanced clinical staging in the p16 positive OPSCC population. Furthermore, while ADI did not correspond with significant differences in survival, multivariate cox regression model demonstrated that “Other” insurance type (Medicaid and uninsured) (hazard ratio [HR] = 10.1, P = .008), age at diagnosis (1.10, P < .001), and advanced clinical staging (HR = 3.25, P = .004) were all significantly associated with increased HR of death. Conclusion While ADI may not be significantly associated with outcomes in HPV‐related OPSCC patients, this study revealed significant sociodemographic and risk factor differences across ADIs, as well as individual factors influencing prognosis. These findings emphasize the need for a comprehensive approach to understanding factors influencing HPV‐related OPSCC incidence and prognosis.